1987
DOI: 10.1002/1097-0142(19870801)60:3+<586::aid-cncr2820601525>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer. Chemotherapy

Abstract: Several chemotherapeutic drugs have been shown to be potentially effective in the patient with metastatic hormone refractory prostate cancer. Individual patients who respond to these chemotherapy agents survive longer than nonresponders, but overall objective response rates for the entire group have been disappointingly small, the length of response short, and there has been no overall survival advantage. Combination chemotherapy has not yet been shown to be superior to single-agent chemotherapy in controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Prostate cancer, the most commonly diagnosed cancer and the second leading cause of cancer death among males in the United States (Boring et al, 1993), is stimulated by androgens, and hormone deprivation is the primary treatment for advanced prostate cancer. Often, the clinical response to androgen withdrawal is temporary and these cancers ultimately recur after which survival is usually less than one year (Gibbons, 1987). It has been suggested that growth factor-mediated autocrine loops, induced by androgens, may contribute to hormone responsive growth and that these autocrine mechanisms may provide the means for cells to survive and continue growth after steroid deprivation (Knabbe et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer, the most commonly diagnosed cancer and the second leading cause of cancer death among males in the United States (Boring et al, 1993), is stimulated by androgens, and hormone deprivation is the primary treatment for advanced prostate cancer. Often, the clinical response to androgen withdrawal is temporary and these cancers ultimately recur after which survival is usually less than one year (Gibbons, 1987). It has been suggested that growth factor-mediated autocrine loops, induced by androgens, may contribute to hormone responsive growth and that these autocrine mechanisms may provide the means for cells to survive and continue growth after steroid deprivation (Knabbe et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…When tumor growth resumes, survival is usually less than 1 year. 4 Failure of androgen ablation is presumably due to the progression of prostatic carcinoma from androgen-dependent to androgen-independent growth. 5 Knowledge of growth-regulatory pathways affected by this transition is limited.…”
mentioning
confidence: 99%
“…While androgen withdrawal initially reduces the growth of metastatic prostatic tumors, this clinical response is temporary and these cancers ultimately recur. At this point, hormonal deprivation therapy fails and survival is usually <1 year (2,3). To further the understanding ofprostate tumor growth and progression, the growth-regulatory pathways associated with the development of androgen-independent tumor cell -growth must be defined.…”
mentioning
confidence: 99%